Haemodynamic response in soccer spectators: is Scottish football exciting?. Issue 6817 (21st December 1991) - Elder, A T; Jyothinagaram, S G; Padfield, P L; Shaw, T R
Abstract : OBJECTIVE–To determine the effect of watching a game of Scottish football on heart rate and blood pressure. DESIGN–Prospective study. SETTING–Two Scottish Premier League football grounds. SUBJECTS–10 healthy men, each a supporter of one of two clubs. MAIN OUTCOME MEASURES–Systolic and diastolic blood pressure and heart rate at home, while walking, and during the match. RESULTS–Systolic blood pressure and heart rate were significantly higher when the men were watching the match than when they were at home. While they were watching the match, heart rate was maximal immediately after a goal had been scored by the supported team. CONCLUSION–The emotional stress invoked by Scottish football is associated with significant increases in heart rate and systolic blood pressure.